Integrative Metabolomics, Proteomics and Transcriptomics Analysis Reveals Liver Toxicity of Mesoporous Silica Nanoparticles - Li, Jing; Sun, Runbin; Xu, Hui; Wang, Guangji (Frontiers in Pharmacology, 2022)
As pharmaceutical excipients, mesoporous silica nanoparticles (MSNs) have attracted considerable concern based on potential risks to the public. The impact of MSNs on biochemical metabolism is poorly understood, and few studies have compared the effects of MSNs administered via different routes. To evaluate the hepatotoxicity of MSNs, metabolomics, proteomics and transcriptomic analyses were performed in mice after intravenous (20 mg/kg/d) or oral ad-ministration (200 mg/kg/d) of MSNs for 10 days. Intravenous injection induced significant hepatic injury based on pathological inspection and increased the levels of AST/ALT and the inflammatory factors IL-6, IL-1β and TNF-a. Omics data suggested intravenous administration of MSNs perturbed the following metabolites: succinate, hypoxanthine, GSSG, NADP+, NADPH and 6-phosphogluconic acid. In addition, increases in GPX, SOD3, G6PD, HK, and PFK at proteomic and transcriptomic levels suggested elevation of glycolysis and pentose phosphate pathway, synthesis of glutathione and nucleotides, and antioxidative pathway activity, whereas oxidative phosphorylation, TCA and mitochondrial energy metabolism were reduced. On the other hand, oral administration of MSNs disturbed inflammatory factors and metabolites of ribose-5-phosphate, 6-phosphogluconate, GSSG, and NADP+ associated with the pentose phosphate pathway, glutathione synthesis and oxidative stress albeit to a lesser extent than intravenous injection despite the administration of a ten-fold greater dose. Overall, systematic biological data suggested that intravenous injection of nanoparticles of pharmaceutical excipients substantially affected hepatic metabolism function and induced oxidative stress and inflammation, whereas oral administration exhibited milder effects compared with intravenous injection.